Lithium composite oxide and its manufacturing method
By incorporating metal substitution elements into lithium composite oxides with a zigzag layered and single-layered structure, the output characteristics of lithium secondary batteries are enhanced, addressing the low output issue and achieving higher capacity and performance.
Patent Information
- Application Number
- JP2020142875
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-22
- Filing Date
- 2020-08-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-08-26
AI Technical Summary
Lithium composite oxides used in lithium secondary batteries exhibit low output characteristics despite having high capacity, which is a limitation for achieving high performance in these batteries.
The development of lithium composite oxides with a specific crystal structure, such as a zigzag layered structure and a single-layered structure, incorporating metal substitution elements like Al, Co, Cu, Fe, Mg, Mn, Ni, Ti, V, W, Zn, and Zr, to enhance output characteristics.
The modified lithium composite oxides demonstrate improved discharge capacity and output characteristics, enabling lithium secondary batteries with higher capacity and output while potentially reducing production costs.
Smart Images

Figure 0007622934000003 
Figure 0007622934000004 
Figure 0007622934000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium composite oxide and a method for producing the same, and more particularly to a lithium composite oxide substituted with a different metal and having improved output characteristics, and a method for producing the same. [Background technology]
[0002] Lithium composite oxides are generally used as the positive electrode active material for lithium secondary batteries. Lithium composite oxides, specifically lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), etc., are widely used as the positive electrode active material for lithium secondary batteries distributed around the world. Active research is being conducted on these lithium composite oxides to improve their characteristics (higher capacity, higher output, cycle stability) and safety.
[0003] As a positive electrode active material for lithium secondary batteries that meets these goals, Li2O3, which is composed of lithium (Li), nickel (Ni), cobalt (Co), manganese (Mn) and oxygen (O), has been developed. x Ni 1-y-z Co y Mn z Li consisting of O2 (NCM), Li, Ni, Co, aluminum (Al) and O x Ni 1-y-z Co y Al z These materials use less Co than existing lithium composite oxides, improving safety, and use cheaper metals. The discharge capacity is also higher than LiCoO2, at about 165mAh / g for NCM and about 200mAh / g for NCA.
[0004] Regarding performance improvements of such lithium secondary batteries, particular attention has been focused on increasing capacity, and a lithium composite oxide represented by LiMnO2, which has a zigzag layered crystal structure as the parent structure and has an α-NaFeO2 type layered structure domain, has been disclosed as a high-capacity material (see Patent Document 1).
[0005] LiMnO2, which is characterized by being composed of at least one of orthorhombic and monoclinic crystals, has been disclosed (see Patent Documents 2 and 3), and its discharge capacity was low at about 170 mAh / g. However, in Patent Document 1, the crystal structure was modified by a process of mechanical milling followed by heat treatment, and the material was further improved as a positive electrode active material with a high discharge capacity of 260 mAh / g. LiMnO2 has been found to be a high-capacity yet inexpensive positive electrode active material for lithium secondary batteries, but it has the problem of low output characteristics.
[0006] In view of the problem of low output characteristics, the present invention provides a lithium composite oxide and a method for producing the same, in which a different metal element is substituted for a manganese compound to produce a metal composite oxide, which is then mixed with a lithium compound and sintered to change the crystal structure from that of existing LiMnO2 and improve the output characteristics. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2019-153564 A [Patent Document 2] JP 2003-007297 A [Patent Document 3] JP 2002-145619 A Summary of the Invention [Problem to be solved by the invention]
[0008] As electronic devices have become smaller and lighter in recent years, research into lithium secondary batteries has been progressing to develop batteries with superior electrochemical properties, such as higher capacity, higher voltage, and higher output. In particular, as described in the Background Art, the development of active materials for the practical application of positive electrode materials for lithium secondary batteries has been in progress. Higher output is essential and required. The present invention aims to satisfy the demand for higher output and resides in a lithium composite oxide for obtaining a positive electrode active material for a lithium secondary battery having excellent electrochemical properties, and a method for producing the same.
Means for Solving the Problems
[0009] As a result of intensive studies to solve the above problems, the present inventors have found a lithium composite oxide containing a metal substitution element (particularly, an element selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr) in LiMnO₂ having a cotyledon crystal and a monoclinic crystal, and have completed the present invention. That is, the present invention has a composition formula Li x Me y Mn 1-y O₂ (where 0 < x ≤ 1.2 and 0 < y ≤ 0.2. Me is one or more metal elements selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr).), having a zigzag layered structure of the orthorhombic system as a mother structure, having domains of a monoclinic or rhombohedral α-NaFeO₂ type layered structure, and having an intensity ratio (A / B) of the diffraction peak integrated intensity (A) observed at 15.3 ± 1.0° and the diffraction peak integrated intensity (B) observed at 18.2 ± 1.0° in powder X-ray diffraction of 0.5 or more. The present invention relates to a lithium composite oxide and a method for producing the same.
Advantages of the Invention
[0010] The positive electrode active material using the lithium composite oxide of the present invention has a structure in which different metals are substituted, and thus has a remarkable effect that the discharge capacity can be improved and the output characteristics can be enhanced. By applying such a positive electrode active material to a battery, it is expected to provide a lithium secondary battery that has a high capacity and a high output while suppressing the cost.
Brief Description of the Drawings
[0011] [Figure 1] It is a schematic diagram showing a zigzag layered structure of the orthorhombic system. [Diagram 2] It is a schematic diagram showing a layered structure (2a) and a rock salt type structure (2b). [Diagram 3](3a) shows the XRD patterns of the lithium composite oxides of Examples 1 to 5 and Comparative Examples 1 and 2, and (3b) shows the XRD patterns of the lithium composite oxides of Examples 6 to 12.
[0012] [Figure 4] It is a figure which showed the XRD pattern of the lithium composite oxide of Example 2, 6, and Comparative Example 2. [Diagram 5] (5a) shows the discharge curves at 0.3C of the positive electrodes in Examples 2, 5, 6 and Comparative Example 2, and (5b) shows the discharge curves at 0.3C of the positive electrodes in Examples 8, 10, 12 and Comparative Example 2. [Figure 6] It is a figure which showed the SEM image of each lithium composite oxide of Example 6, 13.
Mode for Carrying Out the Invention
[0013] Hereinafter, the present invention will be described in detail. The lithium composite oxide of the present invention has the composition formula Li x Me y Mn 1-y O2 (where 0 < x ≤ 1.2 and 0 < y ≤ 0.2), and a different metal is substituted for manganese.
[0014] The different metal is one or more metals selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr, and among them, it is preferably one or more metals selected from the group consisting of Al, Co, Fe, Mg, Nb, Ni, Ti, and Zn. The substitution amount of the different metal is not particularly limited, but is preferably 20.0 mol% or less of manganese, and more preferably 1.0 to 10.0 mol%.
[0015] The lithium composite oxide of the present invention has an orthorhombic zigzag layer structure as a parent structure and a domain of a monoclinic or rhombohedral α-NaFeO2 type layer structure. By having an orthorhombic zigzag layer structure as a parent structure and a domain of a monoclinic or rhombohedral α-NaFeO2 type layer structure, it is possible to exhibit high capacity from the initial cycle without requiring an initial activation charge-discharge cycle, which is advantageous over orthorhombic LiMnO2 that is activated by performing several tens of charge-discharge cycles to exhibit high capacity.
[0016] Here, the orthorhombic zigzag layered structure means that it belongs to the space group Pmnm. A schematic diagram of the orthorhombic zigzag layered structure is shown in Figure 1. Also, schematic diagrams of a layered structure and a rock salt type structure, which are different from the orthorhombic zigzag layered structure, are shown in Figure 2 (2a) and (2b), respectively. As can be seen from Figures 1 and 2, the orthorhombic zigzag layered structure is a crystal structure in which the layers in the α-NaFeO2 type layered structure grow alternately up and down in a regular manner, forming a zigzag layered structure.
[0017] The domain of monoclinic or rhombohedral α-NaFeO2 type layer structure means that it belongs to the space group C2 / m, R-3m or Fm-3m. The domain of monoclinic or rhombohedral α-NaFeO2 type layer structure means that the orthogonal crystal and the monoclinic or rhombohedral crystal form an intergrowth structure with stacking faults.
[0018] The lithium composite oxide of the present invention is characterized in that the intensity ratio (A / B) between the integrated intensity (A) of a diffraction peak observed at 15.3±1.0° and the integrated intensity (B) of a diffraction peak observed at 18.2±1.0° in powder X-ray diffraction measured under the following conditions is 0.5 or more. [Measurement conditions] ·X-ray source: CuKα ray = 1.5418Å Divergence slit: 1 / 2° Scattering slit: 1° Receiving slit: 2mm Step size: 0.01° Scan speed: 0.5° / min
[0019] If the intensity ratio (A / B) is less than 0.5, the lithium composite oxide will have a monoclinic or rhombohedral α-NaFeO2 type layer structure as the main phase and a domain of an orthorhombic zigzag layer structure, which may cause significant cycle deterioration.The intensity ratio (A / B) is preferably 1.0 to 146.0, more preferably 2.6 to 33.6.
[0020] The BET specific surface area of the lithium composite oxide of the present invention is not particularly limited, but is preferably 8.0 m 2 / g or less is preferable, and 2.0 to 7.0 m 2 In addition, as described later, when the lithium composite oxide of the present invention is composited with a carbon or metal composite agent, the BET specific surface area is preferably 10.0 to 60.0 m 2 / g is preferable, and 10.0 to 40.0 m 2 In this case, the BET specific surface area increases in proportion to the mixing ratio of the lithium composite oxide to the above-mentioned complexing agent and the specific surface area of the above-mentioned complexing agent. The BET specific surface area of the lithium composite oxide was calculated by converting the adsorption isotherm obtained from the physical gas adsorption into a BET plot, and calculating the gas adsorption amount V of the monolayer based on the BET isotherm. m The specific surface area can be calculated based on the molecular size of the gas used for physical adsorption, which is known as the BET method.
[0021] The particle size of the lithium composite oxide of the present invention is represented by the average particle size (D50) calculated from the particle size distribution by a laser diffraction / scattering method. The average particle size (D50) of the lithium composite oxide of the present invention is not particularly limited, but is preferably 0.2 to 5.0 μm. The thickness is more preferably 0.5 to 3.0 μm, and further preferably 0.5 to 2.5 μm. The lithium composite oxide of the present invention can further improve electrochemical properties such as output properties by forming a composite lithium composite oxide in which conductive carbon or metal is preferably composited on the surface. Carbon and metal may be used in combination. The above-mentioned composite of the lithium composite oxide is performed for the purpose of uniformly dispersing the active material and the composite agent containing carbon or metal in the electrode. The lithium composite oxide of the active material has a wide range of average particle diameters of secondary particles of 2.0 to 40.0 μm, so that an electrode having a non-uniform conductive path is formed. On the other hand, the above-mentioned composite lithium composite oxide has an advantage that the secondary particles can be crushed and uniformly mixed with the composite agent during the composite process with carbon or metal, and a uniform electrode can be formed.
[0022] Examples of carbon used to obtain the composite lithium composite oxide include graphene, carbon nanotubes, and carbon black such as acetylene black and ketjen black, and in particular, acetylene black or ketjen black is preferred from the viewpoint of cost. Examples of the metal include silver, copper, gold, aluminum, cobalt, zinc, and nickel, and in particular, aluminum, which is also used as a current collector for electrodes, is preferred.
[0023] The lithium composite oxide of the present invention has the composition formula (Me y Mn 1-y ) a O b (However, 1.3 x Me y Mn 1-y A step of preparing a lithium composite oxide represented by LiO2, and x Me y Mn 1-y It can be produced by mechanical milling O2 followed by heat treatment in an inert gas. There is no particular limitation on the raw material of the metal used in the production, and examples thereof include sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides, but there is no limitation thereto.
[0024] In the production of the lithium composite oxide of the present invention, the manganese compound is represented by the composition formula (Me y Mn 1-y ) a O b (However, 1.3 a ], hydroxide [(Me Mn)(OH) b ], oxyhydroxide [(Me Mn)(OOH) c ], oxide [(Me Mn)O d In the formula, a, b, c, and d are numbers satisfying the atomic valence.
[0025] There is no particular limitation on the raw metal material used in the production of the lithium composite oxide, and examples thereof include sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides, but there is no limitation to these. The above manganese compounds are converted into manganese oxides by sintering in air at 600 to 900°C for 12 to 24 hours.
[0026] When the average oxidation number of the metal ion in the manganese compound is less than 2.6, the Mn3O4 composition (Mn y Me 1-y )3O4, and if it exceeds 3.3, the composition MnO2 is Mn y Me1-y When these manganese compounds and lithium compounds are mixed and sintered, the main phase becomes Li with a zigzag layer structure. x Me y Mn 1-y Although lithium composite oxide represented by the formula O2 can be obtained, monoclinic or rhombohedral α-NaFe Since it does not have a domain of an O2 type layer structure, it is not possible to improve the output characteristics. "Preparing in advance an aqueous solution of a metal salt of a substitution element and manganese so as to obtain a preferable Me / Mn molar ratio" means producing a manganese compound with a Me / Mn molar ratio according to the charged composition.
[0027] In the production of the lithium composite oxide of the present invention, the lithium compound to be mixed with the manganese compound is not particularly limited, and examples thereof include, but are not limited to, lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, lithium chloride, lithium iodide, lithium oxalate, lithium sulfate, and lithium oxide. The sintering of the manganese compound and the lithium compound is not particularly limited, but is preferably carried out, for example, at 700 to 1000°C for 6 to 24 hours in an inert gas, and the mechanical milling is preferably carried out, for example, at 300 to 800 rpm for 6 to 72 hours.
[0028] The mechanical milling is preferably carried out in an inert gas atmosphere using balls made of the same material as the container, in a sealed container. The materials of the sealed container and balls are not particularly limited, but examples thereof include, but are not limited to, silicon nitride, zirconia, stainless steel, tungsten carbide, sintered alumina, etc.
[0029] The heat treatment performed after the mechanical milling is not particularly limited, but is preferably performed in an inert gas at 500 to 900°C for 1 to 24 hours, and more preferably at 500 to 700°C for 1 to 12 hours.
[0030] The lithium composite oxide of the present invention also has a metal composition of Me y Mn 1-y(However, y satisfies 0 < y ≤ 0.2, and Me is one or more metals selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr). The manganese compound represented by the formula can be produced by mixing the manganese compound with the above lithium compound and performing hydrothermal treatment in an alkaline aqueous solution.
[0031] The alkaline aqueous solution in which the above hydrothermal treatment is performed refers to, for example, a mixed solution of lithium hydroxide and potassium hydroxide. The pH of the alkaline aqueous solution is preferably, for example, 11.0 to 13.5. The temperature of the above hydrothermal treatment is not particularly limited, but for example, it is preferably 150 °C or higher for 1 hour or more, and more preferably 180 to 240 °C for 4 to 24 hours. The mixing ratio (Li / Mn + Me) of the manganese compound and the lithium compound in the above hydrothermal treatment is not particularly limited, but is preferably 1.5 or more, and more preferably 2.0 to 4.0. The pH of the above hydrothermal treatment is not particularly limited, but is preferably 11 or more, and more preferably 12.0 to 13.5.
[0032] In the present invention, preferred compounding means for producing the above composite lithium composite oxide include mechanical milling of a lithium composite oxide and conductive carbon or metal. Mechanical milling is preferably performed in a sealed container using balls made of the same material as the container. The materials of the sealed container and the balls are not particularly limited, but preferably include silicon nitride, zirconia, stainless steel, tungsten carbide, sintered alumina, etc., but are not limited thereto.
[0033] In order to produce a composite lithium composite oxide, the mechanical milling is preferably performed at a lower speed and for a shorter time than the conditions for producing a lithium composite oxide, since if the mechanical milling is performed for a long time at a high speed, in addition to pulverizing the secondary particles of the active material, the crystal structure having a cubic zigzag layer structure as the mother structure and a monoclinic or rhombohedral α-NaFeO2 type layer structure domain may change to a rock salt structure. In order to more appropriately pulverize and composite the secondary particles of the active material, the mechanical milling is preferably performed at 100 to 600 rpm for 1 to 24 hours, for example. It is more preferable to rotate the rotor at 100 to 300 rpm for 2 to 12 hours.
[0034] The electrode (positive electrode) of the present invention is characterized by containing the lithium composite oxide of the present invention as a positive electrode active material, and preferably further contains a conductive material and a binder in addition to the lithium composite oxide. The conductive carbon or metal, which is the complexing agent in the composite lithium composite oxide, can also function as the conductive material here, apart from the above-mentioned complexing process. As the conductive material here, a conductive polymer other than the carbon or metal, which is the complexing agent in the composite lithium composite oxide, can also be used. Of course, the carbon or metal, which is the complexing agent in the composite lithium composite oxide, can also be used. The content of the conductive material relative to the lithium composite oxide in the electrode (positive electrode) of the present invention is not particularly limited, but is preferably 1 to 10% by weight.
[0035] Examples of the binder include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinyl chloride (PVC), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), but there are no particular limitations. The content of the binder in the electrode (positive electrode) of the present invention is not particularly limited, but is preferably, for example, 1 to 10% by weight.
[0036] In the present invention, the configuration of the lithium secondary battery other than the positive electrode can be as follows, but is not particularly limited. The negative electrode is made of a material that reversibly absorbs and releases Li, such as a carbon-based material, a tin oxide-based material, a silicon oxide-based material, or Li4Ti5O 12 , and materials that form alloys with Li.
[0037] Examples of the electrolyte include organic electrolyte solutions in which Li salts and various additives are dissolved in an organic solvent, ionic liquids, Li-ion conductive solid electrolytes, and combinations of these. The organic solvents of the electrolyte are not particularly limited, but examples include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), and diethyl carbonate (DEC). The electrolyte salts include tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), fluoromethanesulfonylimide (FSI - ), trifluoromethanesulfonylimide (TFSI - ), trifluoromethanesulfonate (CF3SO3 - ) are examples, but there is no particular limitation. EXAMPLES
[0038] The present invention will be described in more detail below by way of examples, but the present invention should not be construed as being limited to these examples in any way.
[0039] <Confirmation of crystal structure> The crystal structure of the lithium composite oxide was identified using a powder XRD (product name: Ultima IV, manufactured by Rigaku Corporation). The measurement conditions were as follows: Target: Cu / Kα Output: 8.0kW (200mA-40kV) Data interval: 0.01° or 0.04° (2θ / θ) Measurement range: 10~20°(1.0° / min) or 10~90°(5° / min)
[0040] <Composition analysis> The compositions of the prepared oxyhydroxide precursor and the lithium composite oxide cathode active material were analyzed by ICP-AES (trade name: Optima5300DV, manufactured by PerkinElmer). .
[0041] <Measurement of BET specific surface area> 1 g of the sample was placed in a glass cell for BET specific surface area measurement, and dehydration treatment was performed at 150 °C for 1 hour under a nitrogen stream to remove the moisture adhering to the powder particles. The treated sample was measured for BET specific surface area by the one-point method using nitrogen gas with a BET measuring device (trade name: Micromeritics FlowsorbIII, manufactured by Shimadzu Corporation).
[0042] <Measurement of average particle diameter (D50)> Using a particle size distribution measuring device (trade name: MT3000II series, manufactured by MicrotracBEL), the average particle diameter (D50) was determined from the particle size distribution diagram. The measurement was carried out after adding an appropriate amount of the cathode active material to pure water and subjecting it to ultrasonic dispersion for 5 minutes.
[0043] <Fabrication of battery> The lithium composite oxide obtained in the examples and comparative examples, the conductive material (trade name: Denka Black, manufactured by Denka), and the binder (10 wt% PvdF / N-Methyl-2-Pyrrolidone solution) were mixed at a weight ratio of 80:10:10 using an agate mortar, and further homogenized with a mixer (AR-100, manufactured by Thinky) to prepare a cathode material ink. The obtained cathode material ink was applied to an aluminum foil with a thickness of 110 μm, dried at 80 °C for 2 hours and dried under reduced pressure at 150 °C for 12 hours or more, and then cut into a circle with a diameter of 16 mm. The cut electrode was uniaxially pressed at 50 kN / cm 2 and dried under reduced pressure at 150 °C for 2 hours to obtain a cathode.
[0044] The lithium secondary battery was constructed with the exception of the positive electrode, using a 1.0M LiPF6 solution in a 1:2 volumetric mixture of EC and DMC as the electrolyte, Celgard 2400 (diameter 26 mm, manufactured by Celgard Corporation) as the separator, and lithium foil (diameter 18 mm, thickness 200 μm, manufactured by Honjo Metals Co., Ltd.) as the negative electrode.
[0045] <Charge / discharge cycle test> The performance evaluation of the prepared positive electrode and battery was carried out at 25°C using a charge / discharge evaluation device (product name: BTS2004W, manufactured by NAGANO Co., Ltd.). Measurements were performed by charging and discharging at a current density of 0.3 C in the potential range of 4.8 V to 1.5 V. The C-rate was calculated at 0.3 C (70 mA / g) with a practical discharge capacity of 230 mAh / g.
[0046] Example 1 Cobalt sulfate (CoSO4) and manganese sulfate (MnSO4) were dissolved in pure water to obtain an aqueous solution containing 0.025 mol / L (liter) of cobalt sulfate and 1.975 mol / L of manganese sulfate, which was used as the metal salt aqueous solution. The total concentration of all metals in the metal salt aqueous solution was 2.0 mol / L. After placing 200 g of pure water in a 1.0 L reaction vessel, the temperature was raised to 60°C and the mixture was stirred and maintained. The above metal salt aqueous solution was added to the reaction vessel at a feed rate of 0.75 g / min. During the above feed operation, air was continuously bubbled into the reaction vessel as an oxidant at a feed rate of 1.0 L / min. Furthermore, 2.0 mol / L of sodium hydroxide aqueous solution was intermittently added and mixed so that the mixed liquid had a pH of 8.5. The precipitated slurry obtained by the reaction was filtered, washed, and then dried at 120°C for 12 hours to obtain manganese oxide containing Mn and Co (theoretical composition (Co 0.025 Mn 0.975 )3O4) was obtained.
[0047] The manganese oxide obtained above was calcined in air at 700°C for 12 hours to obtain a theoretical composition (Co 0.025 Mn 0.975Based on the weight ratio of the metal composition obtained by ICP, manganese oxide and commercially available lithium carbonate (Li2CO3, manufactured by Rare Metallic Co., Ltd.) were dry mixed in a mortar for 20 minutes so that the Li / (Co+Mn) molar ratio was 1.0. The powder mixture was placed in a baking dish and heated in Ar gas at 900°C for 12 hours. It was then cooled to room temperature to obtain LiCo alloy with a zigzag layer structure as the main phase. 0.025 Mn 0.975 The heating and cooling rates were set to 10°C / min.
[0048] The obtained LiCo 0.025 Mn 0.975 O2 was mechanically milled at 600 rpm for 36 hours in a sealed container in an Ar atmosphere to obtain rock salt LiCo 0.025 Mn 0.975 Mechanical milling was performed using zirconia, with 3 balls of 10 mm diameter, 10 balls of 5 mm diameter, and 2 g of balls of 1 mm diameter placed in 1.5 g of the lithium composite oxide sample.
[0049] Next, LiCo with a rock-salt structure 0.025 Mn 0.975 The LiCoO2 was heat-treated at 600°C for 12 hours in Ar gas to form a LiCoFe2O3 layer with a zigzag layered structure as the parent structure and an α-NaFeO2 layered structure domain. 0.025 Mn 0.975 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>.
[0050] Example 2 A lithium composite oxide was produced in the same manner as in Example 1, except that the metal salt aqueous solution used contained 0.05 mol / L of cobalt sulfate and 1.95 mol / L of manganese sulfate, and a battery was then fabricated.
[0051] Example 3 A lithium composite oxide was produced in the same manner as in Example 2, except that manganese oxide and commercially available lithium carbonate were dry-mixed in a mortar for 20 minutes so that the Li / (Co+Mn) molar ratio was 1.05, and a battery was then produced.
[0052] Example 4 The metal salt aqueous solution used contained 0.025 mol / L iron sulfate (III) (Fe2(SO4)3) and 1.975 mol / L manganese sulfate. The total concentration of all metals in the metal salt aqueous solution was 2.0 mol / L. After placing 200 g of pure water in a 1.0 L reaction vessel, the temperature was raised to 60°C and the mixture was stirred and maintained. The above metal salt aqueous solution was added to the reaction vessel at a feed rate of 0.75 g / min. During the above feed operation, air was continuously bubbled into the reaction vessel as an oxidant at a feed rate of 1.0 L / min. Furthermore, 2.0 mol / L of sodium hydroxide aqueous solution was intermittently added and mixed so that the mixed liquid had a pH of 8.5. The precipitated slurry obtained by the reaction was filtered, washed, and then dried at 120°C for 12 hours to obtain manganese oxide containing Mn and Fe (theoretical composition (Fe 0.025 Mn 0.975 )3O4) was obtained.
[0053] The manganese oxide obtained above was calcined in air at 700°C for 12 hours to obtain a manganese oxide with the theoretical composition (Fe 0.025 Mn 0.975 Based on the weight ratio of the metal composition obtained by ICP, manganese oxide and commercially available lithium carbonate were dry mixed in a mortar for 20 minutes so that the Li / (Fe+Mn) molar ratio was 1.0. The resulting mixed powder was placed in a sintering dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature to produce LiFe2O3 with a zigzag layered structure as the main phase. 0.025 Mn 0.975 The heating and cooling rates were set to 10°C / min.
[0054] Obtained LiFe 0.025 Mn 0.975 O2 was mechanically milled in a sealed container in an Ar atmosphere at 600 rpm for 36 hours to obtain rock salt LiFe 0.025 Mn0.975 O2 was obtained. Zirconia was used for mechanical milling, and 1.5 g of lithium composite oxide sample was milled with three 10 mm diameter balls, ten 5 mm diameter balls, and 2 g of 1 mm diameter balls. I put it in.
[0055] Next, LiFe with a rock-salt structure 0.025 Mn 0.975 The LiFeO2 was heat-treated at 600°C for 12 hours in Ar gas to obtain a LiFePO4 nanoparticle with a zigzag layered structure as the parent structure and an α-NaFeO2 layered structure domain. 0.025 Mn 0.975 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>.
[0056] Example 5 A lithium composite oxide was produced in the same manner as in Example 4, except that the metal salt aqueous solution used contained 0.05 mol / L of iron sulfate (III) and 1.95 mol / L of manganese sulfate, and a battery was then fabricated.
[0057] Example 6 The metal salt aqueous solution used contained 0.025 mol / L nickel sulfate (NiSO4), 0.025 mol / L titanyl sulfate (TiOSO4), and 1.95 mol / L manganese sulfate. The total concentration of all metals in the metal salt aqueous solution was 2.0 mol / L. After placing 200 g of pure water in a 1.0 L reaction vessel, the temperature was raised to 60°C and the mixture was stirred and maintained. The above metal salt aqueous solution was added to the reaction vessel at a feed rate of 0.75 g / min. During the above feed operation, air was continuously bubbled into the reaction vessel as an oxidant at a feed rate of 1.0 L / min. Furthermore, 2.0 mol / L of sodium hydroxide aqueous solution was intermittently added and mixed so that the mixed liquid had a pH of 8.5. The precipitated slurry obtained by the reaction was filtered, washed, and then dried at 120°C for 12 hours to obtain manganese oxide containing Mn, Ni, and Ti (theoretical composition (Ni 0.025 Ti 0.025 Mn 0.95 )3O4) was obtained.
[0058] The manganese oxide obtained above was calcined in air at 700°C for 12 hours to obtain a manganese oxide with the theoretical composition (Ni 0.025 Ti 0.025 Mn 0.95 Based on the weight ratio of the metal composition obtained by ICP, manganese oxide and commercially available lithium carbonate were dry mixed in a mortar for 20 minutes so that the Li / (Ni+Ti+Mn) molar ratio was 1.0. The resulting mixed powder was placed in a sintering dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature to produce LiNi 0.025 Ti 0.025 Mn 0.95 The heating and cooling rates were set to 10°C / min.
[0059] The obtained LiNi 0.025 Ti 0.025 Mn 0.95 O2 was mechanically milled in a sealed container in an Ar atmosphere at 600 rpm for 36 hours to obtain rock salt LiNi 0.025 Ti 0.025 Mn 0.95 Mechanical milling was performed using zirconia, with 3 balls of 10 mm diameter, 10 balls of 5 mm diameter, and 2 g of balls of 1 mm diameter placed in 1.5 g of the lithium composite oxide sample.
[0060] Next, LiNi with a rock salt structure 0.025 Ti 0.025 Mn 0.95 The LiNiFeO2 was heat-treated at 600°C for 12 hours in Ar gas to form a LiNiFeO2-type layered structure with a zigzag layered structure as the parent structure. 0.025 Ti 0.025 Mn 0.95 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>.
[0061] Example 7 A lithium composite oxide was produced in the same manner as in Example 6, except that manganese oxide and commercially available lithium carbonate were dry-mixed in a mortar for 20 minutes so that the Li / (Ni+Mn) molar ratio was 1.05, and a battery was then fabricated.
[0062] Example 8 The metal salt aqueous solution used contained 0.025 mol / L magnesium sulfate (MgSO4), 0.025 mol / L titanyl sulfate, and 1.95 mol / L manganese sulfate. The total concentration of all metals in the metal salt aqueous solution was 2.0 mol / L. After placing 200 g of pure water in a 1.0 L reaction vessel, the temperature was raised to 60°C and the mixture was stirred and maintained. The above metal salt aqueous solution was added to the reaction vessel at a feed rate of 0.75 g / min. During the above feed operation, air was continuously bubbled into the reaction vessel as an oxidant at a feed rate of 1.0 L / min. Furthermore, 2.0 mol / L of sodium hydroxide aqueous solution was intermittently added and mixed so that the mixed liquid had a pH of 8.5. The precipitated slurry obtained by the reaction was filtered, washed, and then dried at 120°C for 12 hours to obtain manganese oxide containing Mn, Mg, and Ti (theoretical composition (Mg 0.025 Ti 0.025 Mn 0.95 )3O4) was obtained.
[0063] The manganese oxide obtained above was calcined in air at 700°C for 12 hours to obtain a manganese oxide with the theoretical composition (Mg 0.025 Ti 0.025 Mn 0.95 Based on the weight ratio of the metal composition obtained by ICP, manganese oxide and commercially available lithium carbonate were dry mixed in a mortar for 20 minutes so that the Li / (Mg+Ti+Mn) molar ratio was 1.0. The resulting mixed powder was placed in a sintering dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature to produce LiMgO with a zigzag layered structure as the main phase. 0.025 Ti 0.025 Mn 0.95 The heating and cooling rates were set to 10°C / min.
[0064] The obtained LiMg 0.025 Ti 0.025 Mn0.95 O2 was mechanically milled in a sealed container in an Ar atmosphere at 600 rpm for 36 hours to obtain rock salt LiMg 0.025 Ti 0.025 Mn 0.95 Mechanical milling was performed using zirconia, with 3 balls of 10 mm diameter, 10 balls of 5 mm diameter, and 2 g of balls of 1 mm diameter placed in 1.5 g of the lithium composite oxide sample.
[0065] Next, LiMg 0.025 Ti 0.025 Mn 0.95 The LiMgO2 was heat-treated at 600°C for 12 hours in Ar gas to form a LiMgO2 composite with a zigzag layered structure as the parent structure and an α-NaFeO2 layered structure domain. 0.025 Ti 0.025 Mn 0.95 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>.
[0066] Example 9 The same procedure as in Example 8 was used to prepare LiMg 0.05 Ti 0.05 Mn 0.9 An O2 lithium composite oxide was produced, and then a battery was fabricated.
[0067] Example 10 The metal salt aqueous solution used contained 0.025 mol / L zinc sulfate (ZnSO4), 0.025 mol / L titanyl sulfate, and 1.95 mol / L manganese sulfate. The total concentration of all metals in the metal salt aqueous solution was 2.0 mol / L. After placing 200 g of pure water in a 1.0 L reaction vessel, the temperature was raised to 60°C and the mixture was stirred and maintained. The above metal salt aqueous solution was added to the reaction vessel at a feed rate of 0.75 g / min. During the above feed operation, air was continuously bubbled into the reaction vessel as an oxidant at a feed rate of 1.0 L / min. Furthermore, 2.0 mol / L of sodium hydroxide aqueous solution was intermittently added and mixed so that the mixed liquid had a pH of 9.0. The precipitated slurry obtained by the reaction was filtered, washed, and then dried at 120°C for 12 hours to obtain manganese oxide containing Mn, Zn, and Ti (theoretical composition (Zn 0.025 Ti 0.025 Mn 0.95 )3O4) was obtained.
[0068] The manganese oxide obtained above was calcined in air at 700°C for 12 hours to obtain a manganese oxide with the theoretical composition (Zn 0.025 Ti 0.025 Mn 0.95 Based on the weight ratio of the metal composition obtained by ICP, manganese oxide and commercially available lithium carbonate were dry mixed in a mortar for 20 minutes so that the Li / (Zn+Ti+Mn) molar ratio was 1.0. The resulting mixed powder was placed in a sintering dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature to produce LiZn 0.025 Ti 0.025 Mn 0.95 The heating and cooling rates were set to 10°C / min.
[0069] The obtained LiZn 0.025 Ti 0.025 Mn 0.95 O2 was mechanically milled in a sealed container in an Ar atmosphere at 600 rpm for 36 hours to obtain rock salt LiZn 0.025 Ti 0.025 Mn 0.95 Mechanical milling was performed using zirconia, with 3 balls of 10 mm diameter, 10 balls of 5 mm diameter, and 2 g of balls of 1 mm diameter placed in 1.5 g of the lithium composite oxide sample.
[0070] Next, LiZn with a rock-salt structure 0.025 Ti 0.025 Mn0.95 The LiZnO2 was heat-treated at 600°C for 12 hours in Ar gas to obtain a LiZnFeO2-type layered structure with a zigzag layered structure as the parent structure. 0.025 Ti 0.025 Mn 0.95 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>.
[0071] Example 11 The metal salt aqueous solution used contained 0.05 mol / L magnesium sulfate and 1.95 mol / L manganese sulfate, and the total concentration of all metals in the metal salt aqueous solution was 2.0 mol / L. After placing 200 g of pure water in a 1.0 L reaction vessel, the temperature was raised to 60°C and the mixture was stirred and maintained. The above metal salt aqueous solution was added to the reaction vessel at a feed rate of 0.75 g / min. During the above feed operation, air was continuously bubbled into the reaction vessel as an oxidant at a feed rate of 1.0 L / min. Furthermore, 2.0 mol / L of sodium hydroxide aqueous solution was intermittently added and mixed so that the mixed liquid had a pH of 9.0. The precipitated slurry obtained by the reaction was filtered, washed, and then dried at 120°C for 12 hours to obtain manganese oxide containing Mn and Mg (theoretical composition (Mg 0.05 Mn 0.95 )3O4) was obtained.
[0072] The manganese oxide obtained above was calcined in air at 700°C for 12 hours to obtain a manganese oxide with the theoretical composition (Mg 0.05 Mn 0.95 Based on the weight ratio of the metal composition obtained by ICP, manganese oxide and commercially available lithium carbonate were dry mixed in a mortar for 20 minutes so that the Li / (Mg+Mn) molar ratio was 1.0. The resulting mixed powder was placed in a sintering dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature to produce LiMgO with a zigzag layered structure as the main phase. 0.05 Mn 0.95 The heating and cooling rates were set to 10°C / min.
[0073] The obtained LiMg 0.05 Mn0.95 O2 was mechanically milled in a sealed container in an Ar atmosphere at 600 rpm for 36 hours to obtain rock salt LiMg 0.05 Mn 0.95 Mechanical milling was performed using zirconia, with 3 balls of 10 mm diameter, 10 balls of 5 mm diameter, and 2 g of balls of 1 mm diameter placed in 1.5 g of the lithium composite oxide sample.
[0074] Next, LiMg 0.05 Mn 0.95 The LiMgO2 was heat-treated at 600°C for 12 hours in Ar gas to form a LiMgO2 composite with a zigzag layered structure as the parent structure and an α-NaFeO2 layered structure domain. 0.05 Mn 0.95 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>. did.
[0075] Example 12 Manganese carbonate (MnCO3) is fired in air at 700°C for 12 hours to produce manganese oxide with the theoretical composition (Mn2O3). Manganese oxide, commercially available vanadium oxide (V) (V2O5, Wako Co., Ltd.), and commercially available lithium carbonate are dry-mixed in a mortar for 20 minutes so that the V / (V+Mn) molar ratio of the metal composition is 0.05 and the Li / (V+Mn) molar ratio is 1.0. The resulting mixed powder is placed in a firing dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature to produce LiV, whose main phase has a zigzag layer structure. 0.05 Mn 0.95 The heating and cooling rates were set to 10°C / min.
[0076] The obtained LiV 0.05 Mn 0.95 O2 was mechanically milled at 600 rpm for 36 hours in a sealed vessel under an Ar atmosphere to obtain rock salt LiV. 0.05 Mn 0.95 Mechanical milling was performed using zirconia, with 3 balls of 10 mm diameter, 10 balls of 5 mm diameter, and 2 g of balls of 1 mm diameter placed in 1.5 g of the lithium composite oxide sample. Next, LiV with a rock-salt structure 0.05 Mn 0.95 The LiV with a zigzag layered structure as the parent structure and an α-NaFeO2-type layered structure domain was fabricated by heat-treating the LiV with a zigzag layered structure as the parent structure in Ar gas at 600°C for 12 hours. 0.05 Mn 0.95 A lithium composite oxide of O2 was obtained. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of Battery>.
[0077] Example 13 The LiNiFeO2-type layered structure domain having a zigzag layered structure as obtained in Example 6 was placed in a zirconia sealed container. 0.025 Ti 0.025 Mn 0.95 0.4 g of the O2 lithium composite oxide, 0.05 g of a composite material (product name: Denka Black, manufactured by Denka Co.), three 10 mm diameter balls, ten 5 mm diameter balls, and 2 g of 1 mm diameter balls were put into a container and mechanically milled at 100 rpm for 12 hours to obtain a carbon-composite lithium composite oxide. Next, the obtained carbon-composite lithium composite oxide and a binder (10 wt% PvdF / N-Methyl-2-Pyrrolidone solution) were uniformly mixed in a weight ratio of 90:10 using a mixer to prepare a cathode material ink. A battery was prepared according to the above <Preparation of a battery> except for using the cathode material ink.
[0078] Example 14 The LiNiFeO2-type layered structure domain having a zigzag layered structure as obtained in Example 6 was placed in a zirconia sealed container. 0.025 Ti 0.025 Mn 0.95 0.4 g of O2 lithium composite oxide and carbon nanotubes (Shenzhen A carbon-composite lithium composite oxide was obtained by adding 0.05 g of SUSN Nanotech Co., Ltd., three 10 mm diameter balls, ten 5 mm diameter balls, and 2 g of 1 mm diameter balls and mechanically milling them at 100 rpm for 12 hours. Next, the obtained carbon-composite lithium composite oxide and a binder (10 wt% PvdF / N-Methyl-2-Pyrrolidone solution) were uniformly mixed in a weight ratio of 90:10 using a mixer to prepare a cathode material ink. A battery was prepared according to the above <Preparation of a battery> except for using the cathode material ink.
[0079] Comparative Example 1 Manganese carbonate (MnCO3) was calcined in air at 700°C for 12 hours to produce manganese oxide of theoretical composition (Mn2O3). Manganese oxide and commercially available lithium carbonate were dry mixed in a mortar for 20 minutes so that the Li / Mn molar ratio of the metal composition was 1.0. The resulting mixed powder was placed in a calcination dish and heated in Ar gas at 900°C for 12 hours, then cooled to room temperature and the main The LiMnO2 with a zigzag layered structure was obtained. The heating and cooling rates were 10℃ / min.
[0080] The obtained LiMnO2 was subjected to mechanical milling in a closed vessel in an Ar atmosphere at 600 rpm for 36 hours to obtain rock salt type LiMnO2. Next, LiMnO2 with a rock salt structure was heat-treated in Ar gas at 600℃ for 12 hours to obtain a lithium composite oxide of LiMnO2 with a zigzag layered structure as the parent structure and an α-NaFeO2 layered structure domain. Furthermore, a battery was produced using the obtained lithium composite oxide according to the above <Production of a Battery>.
[0081] Comparative Example 2 A lithium composite oxide was produced in the same manner as in Comparative Example 1, except that LiMnO2 having a rock salt structure was heat-treated in Ar gas at 700°C for 12 hours, and a battery was then fabricated. The preparation conditions and physical properties of Examples 1 to 14 and Comparative Examples 1 and 2 are shown in Table 1.
[0082] [Table 1]
[0083] <Average particle size of lithium composite oxide> The particle size of the lithium composite oxides produced in Examples 1 to 14 and Comparative Examples 1 and 2 was measured. The resulting average particle size (D50) is shown in Table 1. It was confirmed that the lithium composite oxides prepared in the examples did not have a change in particle size distribution due to substitution with different metals (Co, Fe, Ni+Ti, Mg+Ti, Zn+Ti, Mg, V).
[0084] <BET specific surface area of lithium composite oxide> The BET specific surface area of the lithium composite oxides produced in Examples 1 to 14 and Comparative Examples 1 and 2 was measured, and the results are shown in Table 1. It was confirmed that the lithium composite oxides produced in the examples did not have a change in BET specific surface area due to the substitution of different metals.
[0085] <Crystallization of lithium composite oxide> The XRD patterns of the lithium composite oxide powders of Examples 1 to 12 and Comparative Examples 1 and 2 at 10 to 20° were confirmed, and the results are shown in FIG. 3 (3a) and (3b). From Examples 1 to 12 and Comparative Examples 1 and 2 in FIG. 3, the peaks of the orthorhombic (010) plane shown at 15.3±1.0° (A) and the monoclinic (001) plane shown at 18.2±1.0° (B) were confirmed for the lithium composite oxides prepared by the process of the present invention. It was confirmed that the lithium composite oxides prepared by the process of the present invention have a structure in which the orthorhombic system is the parent structure and the monoclinic system is the domain, as shown in FIG. 3. Furthermore, the (A / B) peak integrated intensity ratio was calculated, and the results are shown in Table 1.
[0086] The XRD patterns of the lithium composite oxide powders of Examples 2 and 6 and Comparative Example 2 were confirmed at 10 to 90°, and the results are shown in FIG. 4. It was found that the lithium composite oxide prepared by the process of the present invention has strong peaks on the orthorhombic (010), (011), (200), and (021) planes and a weak peak on the monoclinic (001) plane. In other words, it was found that the lithium composite oxide has an orthorhombic zigzag layer structure as a parent structure and an α-NaFeO2 layer structure domain. Furthermore, it was confirmed that the lithium composite oxide prepared by the process of the present invention does not change its crystal structure consisting of heterometal substitution.
[0087] <High capacity and high output characteristics> Table 2 shows the discharge capacities at 0.3 C, 1.0 C, and 2.0 C obtained by charge / discharge measurement of the positive electrodes using the lithium composite oxides produced in Examples 1 to 14 and Comparative Examples 1 and 2 as the positive electrode active materials, as well as the energy density obtained from the discharge capacity at 0.3 C, the average discharge potential (V), and the electrode density (kg / L).
[0088] [Table 2]
[0089] Furthermore, the results of discharge measurements performed at 0.3 C on the positive electrodes using the lithium composite oxides produced in Examples 2, 5, 6, 8, 10, 12, 13, and 14 and Comparative Example 2 as the positive electrode active material are shown in (5a), (5b), and (5c) of Figure 5. The energy density was calculated as follows. Energy density (Wh / kg) = discharge capacity (Ah / kg) x average discharge potential (V) Energy density (Wh / L) = discharge capacity (Ah / kg) x average discharge potential (V) × Electrode density (kg / L) The electrode density used in the above calculation was calculated from the weight of the positive electrode active material + conductive material + binder excluding the aluminum foil current collector from the electrode prepared according to the description in <Preparation of Battery> above, and the volume calculated from the diameter and thickness of the electrode.
[0090] From the discharge capacity results at 0.3C shown in Table 2, Examples 1 to 14 showed improved output characteristics compared to Comparative Examples 1 and 2 which were manufactured without metal element substitution. The same results were also shown for the discharge capacity at 1.0C and 2.0C. The energy density of the positive electrodes prepared in Examples 1 to 14 shown in Table 2 was also higher than that of Comparative Examples 1 and 2, and lithium secondary batteries with high capacity and high output were achieved. In particular, in Examples 13 and 14, carbon was uniformly distributed around the lithium composite oxide, and the output characteristics were further improved. The results were positive. SEM images of the lithium composite oxides of Examples 6 and 13 are shown in Fig. 6. In Example 13, it was confirmed from the SEM image that the secondary particles of the active material were crushed to a more uniform particle size by forming a carbon composite on the lithium composite oxide of Example 6. [Industrial Applicability]
[0091] The lithium composite oxide of the present invention is expected to be used in the field of positive electrode active materials for lithium secondary batteries as an inexpensive, high-capacity, high-output positive electrode active material.
Claims
1. Composition formula Li x Me y Mn 1-y O 2 (However, 0<x≦1.2 and 0<y≦0.
2. Me is one or more metal elements selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr.) The matrix structure is an orthorhombic zigzag layer structure, and the monoclinic or rhombohedral α-NaFeO 2 A lithium composite oxide characterized in that it has a domain having a layer structure of the above-mentioned type, and that the intensity ratio (A / B) of the integrated intensity (A) of a diffraction peak observed at 15.3±1.0° to the integrated intensity (B) of a diffraction peak observed at 18.2±1.0° in powder X-ray diffraction is 0.5 or more.
2. 2. The lithium composite oxide according to claim 1, wherein Me is at least one metal element selected from the group consisting of Al, Co, Fe, Mg, Nb, Ni, Ti, and Zn.
3. BET specific surface area: 8.0 m 2 The lithium composite oxide according to claim 1 or 2, wherein the average particle size (D50) is 0.2 to 5.0 μm.
4. 4. The lithium composite oxide according to claim 1, which is composited with conductive carbon or metal.
5. The method for producing the lithium composite oxide according to any one of claims 1 to 4, comprising the steps of: y Mn 1-y ) a O b (wherein 1.3<a / b<1.6, 0<y≦0.2, and Me is one or more metals selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr), and a manganese compound having an average oxidation number of the metal ion of 2.6 to 3.3 and a lithium compound are mixed and sintered to produce a Li SiO 2 ... x Me y Mn 1-y O 2 A step of preparing a lithium composite oxide represented by the formula: x Me y Mn 1-y O 2 The method comprises subjecting the resulting material to mechanical milling and then heat treating the material in an inert gas.
6. The method for producing a lithium composite oxide according to any one of claims 1 to 4, wherein the metal composition is Me y Mn 1-y (wherein 0<y≦0.2 and Me is one or more metals selected from the group consisting of Al, Co, Cr, Cu, Fe, Mg, Mo, Nb, Ni, Si, Ti, V, W, Zn, and Zr) is mixed with a lithium compound, and then the mixture is subjected to hydrothermal treatment in an alkaline aqueous solution.
7. 7. The method according to claim 5, further comprising the step of mechanically milling the resulting lithium composite oxide together with a composite agent of conductive carbon or metal.
8. An electrode comprising the lithium composite oxide according to any one of claims 1 to 4.
9. A lithium secondary battery using the electrode according to claim 8 as a positive electrode.
Citation Information
Patent Citations
Lithium iron oxide powder and production of the same
JP1998067520A
Nonaqueous electrolyte lithium secondary cell and manufacture of its positive electrode material
JP1998134812A
Lithium manganese multiple oxide, positive electrode material for lithium secondary cell, positive electrode for lithium secondary cell and manufacturing method of lithium secondary cell and lithium manganese multiple oxide
JP2002145619A
Positive electrode active material for nonaqueous electrolyte secondary battery
JP2003007297A
Lithium transition metal based compound powder, its manufacturing method, and positive electrode material for lithium secondary battery and lithium secondary battery using it
JP2011108554A